Ultrasound-guided Suprainguinal Fascia Iliaca Block for Postoperative Analgesia in Patients Undergoing Femur Fracture Surgery: A Randomized Control Trial Study Comparing Bupivacaine (0.25%) and Bupivacaine (0.125%) - Shadab Ahmed; Sourabh Kumar; Ekramul Haque; Vishwanath Kumar; Shio Priye (Annals of African Medicine, 2026)
Abstract Background: Ultrasound-guided supra-inguinal fascia iliaca compartment block (FICB) is increasingly used for postoperative analgesia in femur fracture surgery. However, evidence comparing different concentrations of bupivacaine for this block remains limited. Objective: The objective of this study is to compare the analgesic efficacy and safety of 0.25% and 0.125% bupivacaine administered through ultrasound-guided supra-inguinal FICB in patients undergoing femur fracture surgery. Materials and Methods: In this prospective, randomized, double-blind controlled trial, 90 American Society of Anesthesiologists I–II patients aged 18–50 years undergoing elective femur fracture fixation under spinal anesthesia were enrolled. Patients were randomized into two groups: Group A ( n = 45) received 20 mL of 0.25% bupivacaine and Group B ( n = 45) received 20 mL of 0.125% bupivacaine for ultrasound-guided supra-inguinal FICB. Postoperative pain scores, rescue analgesic requirements, hemodynamic parameters, sensory blockade, ambulation, and adverse events were assessed. Results: Baseline characteristics were comparable between the groups. Visual Analog Scale scores at rest and during movement 20 min after block administration were significantly lower in Group A ( P < 0.001). Postoperative pain scores remained significantly lower in Group A at 2, 4, 6, and 18 h. Patients receiving 0.25% bupivacaine had significantly greater sensory blockade, lower total rescue analgesic consumption, earlier time to first rescue analgesia, and more stable hemodynamic parameters than those receiving 0.125% bupivacaine ( P < 0.05). No major complications or adverse effects were observed in either group. Conclusion: Ultrasound-guided suprainguinal FICB is an effective and safe technique for postoperative analgesia in femur fracture surgery. Compared with 0.125% bupivacaine, 0.25% bupivacaine provided superior analgesia, prolonged pain relief, reduced analgesic requirements, and better hemodynamic stability.